USM-UNIVERSITY OF LORRAINE FRANCE STRENGTHEN INTERNATIONAL STRATEGIC PARTNERSHIP - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 14 June 2016 Universiti Sains Malaysia (USM) continues to soar on the international stage with a strategic partnership involving University of Lorraine (UoL) France, with the visit today by its VicePresident for Partnerships and International Affairs, Professor Karl Tombre; Head of Strategic International Partnerships, Professor JeanLouis Morel and Head of the International Office, Ms. Nathalie Fick.